Pengaruh Web Design, Brand Awareness, dan Personal Branding CEO Terhadap Keputusan Pembelian Produk Erigo (Studi Kasus Mahasiswa Universitas Islam Malang Angkatan 2020) - Agesta, Rifqi Naufal; Basalamah, Muhammad Ridwan; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Globalization and modernization have created a competitive business environment, including fashion industry. In the midst of these conditions, Indonesian people are starting to switch to choosing local products, including fashion product. Erigo is one of fashion local brand people who are serious about competing in the era of globalization and modernization. The aim of this research is to find out whether web design, brand awareness, and personal branding The CEO influences the decision to purchase Erigo products. This type of research is explanatory research using a quantitative approach. Sampling was carried out on 2020 active students of the University of Islam Malang using the Malhotra formula so that a sample of 85 respondents was obtained. This research method uses multiple linear regression analysis with the SPSS 25 analysis tool. This research shows that web design, brand awareness, andpersonal branding CEO simultaneously has a significant influence on purchasing decisions. Partially, web design significant influence on purchasing decisions. Partially, brand awareness significant influence on purchasing decisions. Partially, personal branding CEO does not have a significant influence on purchasing decisions. Keywords: Web Design, Brand Awareness, Personal Branding CEO, Fashion, Erigo